2017
DOI: 10.1074/jbc.m117.799304
|View full text |Cite
|
Sign up to set email alerts
|

Function of inhibitor of Bruton's tyrosine kinase isoform α (IBTKα) in nonalcoholic steatohepatitis links autophagy and the unfolded protein response

Abstract: Nonalcoholic fatty liver disease (steatosis) is the most prevalent liver disease in the Western world. One of the advanced pathologies is nonalcoholic steatohepatitis (NASH), which is associated with induction of the unfolded protein response (UPR) and disruption of autophagic flux. However, the mechanisms by which these processes contribute to the pathogenesis of human diseases are unclear. Herein, we identify the α isoform of the inhibitor of Bruton's tyrosine kinase (IBTKα) as a member of the UPR, whose exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Antibodies targeting phosphoproteins were incubated with 1 mM sodium orthovanadate in 0.5% BSA/TBS. The following primary antibodies were used: 1:2,000 Vps15 for mouse studies (Novus Biologicals NBP1-30463) 39 , 1:1,000 VPS15 for human studies (Abcam ab124817, Abcam ab128903) 41 , 1:500 Vps34 (Cell Signaling, #3811) 42,43 , 1:1,000 Beclin1 (Cell Signaling #3738) 44 , 1:500 p62 (Novus Biologicals, H00008878-M01) 45 , 1:2,000 GAPDH (Millipore, MAB3 74) 26,46 , 1:1,000 ubiquitin (Santa Cruz, sc-8017) 47 , 1:10,000 α-tubulin (Sigma Aldrich, T6199) 48 , 1:100 LC3 (Nanotools, 0260-100/LC3-2G6) 49 , 1:600 EGFR (Cell Signaling #4267 S) 50 , 1:200 Nischarin (Santa Cruz, sc-365364) 21 , 1:500 PAK1 T423 (Cell Signaling, #2601 S) 51 and 1:500 N -terminal Vps15 antibody (Proteintech, 17894-1-AP). Western blots were quantified using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies targeting phosphoproteins were incubated with 1 mM sodium orthovanadate in 0.5% BSA/TBS. The following primary antibodies were used: 1:2,000 Vps15 for mouse studies (Novus Biologicals NBP1-30463) 39 , 1:1,000 VPS15 for human studies (Abcam ab124817, Abcam ab128903) 41 , 1:500 Vps34 (Cell Signaling, #3811) 42,43 , 1:1,000 Beclin1 (Cell Signaling #3738) 44 , 1:500 p62 (Novus Biologicals, H00008878-M01) 45 , 1:2,000 GAPDH (Millipore, MAB3 74) 26,46 , 1:1,000 ubiquitin (Santa Cruz, sc-8017) 47 , 1:10,000 α-tubulin (Sigma Aldrich, T6199) 48 , 1:100 LC3 (Nanotools, 0260-100/LC3-2G6) 49 , 1:600 EGFR (Cell Signaling #4267 S) 50 , 1:200 Nischarin (Santa Cruz, sc-365364) 21 , 1:500 PAK1 T423 (Cell Signaling, #2601 S) 51 and 1:500 N -terminal Vps15 antibody (Proteintech, 17894-1-AP). Western blots were quantified using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…For example, autophagy is induced to dispose of misfolded proteins remaining after ER-associated protein degradation [93]. Recently, Willy et al investigated an isoform of inhibitor of Burton’s tyrosine kinase (IBTKα) [94], a component of the UPR that resides mainly in the ER and is preferentially translated during ER stress [95]. They showed that IBTKα was up-regulated downstream of PERK-CHOP pathway during palmitate-induced ER stress [95], which was associated with aberrant autophagy linking to consequent inhibition of autophagic flux (Fig.…”
Section: Autophagy and Endoplasmic Reticulum (Er) Stress In Nashmentioning
confidence: 99%
“…Normalization of ER stress markers correlated with weight loss and reduced hepatic lipid content after bariatric surgery (54). Furthermore, activation of the UPR was observed in the livers of obese patients with NASH as well as in mice fed a methionine-cholinedeficient diet (MCDD) exhibiting NASH features without obesity (55)(56)(57)(58). A direct activation of the IRE1α-XBP1 branch was observed in vivo during the development of insulin resistance in the liver (59).…”
mentioning
confidence: 99%